Electronic navigation systems - Tetley, L. (Laurence), 1941-; Calcutt, D. M., 1935-; Tetley, L. (Laurence), 1941- (Oxford ; Boston : Butterworth-Heinemann, 2001)
Maritime navigation has rapidly developed since the publication of the last edition of the title with methods of global position fixing for shipping becoming standardized. As in the previous two editions, this edition will provide a sound basis for the understanding of modern navigation systems and brings the student or professional up-to-date with the latest developments in technology and the growing standardization of maritime navigation techniques. Developed with close scrutiny from the US Merchant Marine Academy and the major maritime navigation centres in the UK, out-dated techniques have been replaced by an expanded section on the now standard Navstar GPS systems and the Integrated Nav. In addition, a new chapter on the application of electronic charts will also be included, as well as problems at the end of each chapter with worked solutions. Thoroughly revised and up-dated to conform to stricter training requirements mandated by the STCW-95 amendments. Expanded section on Navstar GPS systems, the now standard global position fixing technique. Up-dated and expanded section on integrated navigation.
Radio wave propagation and the frequency spectrum -- Depth sounding systems -- Speed measurement -- Loran-C -- Satellite navigation and the GPS -- Integrated bridge systems -- Electronic charts -- The ship's master compass -- Automatic steering -- VHF direction finding -- GMDSS -- Computer functions -- Digital terms -- Dare communications -- NMEA protocol -- USCG Navcen.
Rev. ed. of: Electronic aids to navigation. 1991.
Includes index.
Keywords: Electronics in navigation; Electronic books